Load-bearing characteristics of clamped coal and ground inclined-borehole hydraulic fracturing method for rockburst control in steeply inclined coal seams - Bin YU; Yong LI; Mingxian PENG; Rui GAO; Wenlian YANG; Ming LI; Yang TAI; Ziyu SHANG; Jun DING; Weidong MIAO; Hongjie ZHAO (Meitan xuebao)
Northwestern China, a vital hub for the Belt and Road Initiative and the nation's primary coal producing region, holds significant importance in ensuring energy security. Due to the influence of complex geological evolution, steeply inclined coal seams are widely developed in this region. The unique geological conditions lead to a distinctive “clamping” structure formed by the roof and floor during the mining process, which frequently leads to rockburst hazards. However, the current understanding of the stress and energy distribution of coal under the “clamping” effect and its influencing factors remains insufficient, and current prevention technologies face significant limitations. To address these scientific challenges, based on Timoshenko beam theory, an elastic support mechanical model for the cantilevered roof of steeply inclined coal seams is established. By integrating the quantitative relationship between Winkler elastic foundation support force and deflection, analytical equations for coal load and energy distribution are derived. The effects of roof cantilever length, thickness, and inclination angle on coal load and energy distribution are quantitatively analyzed. Furthermore, an innovative method for mitigating rockburst hazards in steeply inclined coal seams is proposed, involving ground-inclined well regional fracturing to modify the “clamping” structure and regulate the stress environment. The mechanism and effectiveness of this method were preliminarily clarified. The results indicate that coal load and energy exhibit an unimodal distribution, significantly increasing with the extension of cantilever length and roof thickness. When the cantilever length increases from 15 m to 45 m, the peak load rises by a factor of 13 times, while the energy increases by 168 times. Similarly, as the roof thickness increases from 10 m to 22 m, the peak load and energy reach 11.5×109 N and 3.9×1010 J, respectively, with the peak position shifting away from the coal wall. In contrast, the roof inclination has a relatively minor influence on load and energy distribution. Ground-inclined well regional fracturing constructs a grid-like fracture network, segmenting the intact roof into regular fractured rock blocks. This process transforms the traditional periodic roof failure mode from a suspended roof structure into a sliding instability mechanism along fracture planes. Consequently, the “clamping” effect exerted by the roof and floor on the coal seam is fundamentally weakened. Additionally, the dynamic impact load induced by roof failure shifts from sudden impact to progressive release, effectively mitigating rockburst risks. The induced “mining-fracturing” synergistic failure effect leads to the early breakage of critical burst-prone layers, eliminating large-span suspended roofs, shortening the duration of roof suspension, and reducing peak coal seam shear stress by 41.9%. Moreover, the “channeling” effect of fracturing enhances overlying strata fracture development by 31.4 m, increasing the collapse of gangue and improving the filling quality of the goaf under expansion effects. This leads to the formation of a more stable “gangue-roof” bearing system, which not only effectively restrains roof bending deformation but also facilitates stress transfer from the roof to the floor strata.